Impact of crisis communication strategies on people's attitudes toward behavioral guidelines regarding COVID-19 and on their trust in local officials: Online Supplement - Hirschfeld, Gerrit; Thielsch, Meinald T.
This is the online supplement for a study on crisis communication strategies that could be applied by local officials in situations such as the COVID-19 pandemic. The crisis communication patterns of commercial organizations are generally guided by Situational Crisis Communication Theory (SCCT), but the impact of different crisis communication strategies for public messaging on COVID-19 has not been thoroughly examined. As such, we test how crisis communication strategies affect trust in mayors and the acceptance of behavioral measures, specifically regarding the buffering effect of a mayor’s pre-crisis reputation as well whether trust mediates the link between crisis communication strategies and acceptance of behavioral measures. A total of 561 participants (53% female; mean age 50 years) took part in our online experiment in which we systematically manipulated the mayor’s crisis communication strategy (deny vs. diminish, vs. rebuild, vs. bolstering, vs. no response) and pre-crisis reputation (good past crisis management, bad past crisis management). Age, gender and education served as covariates. In an exploratory analysis, we also tested the predictive power of personal concern regarding the COVID-19 pandemic as well as internal and external control convictions. The study was approved by the ethics committee of the Faculty of Psychology & Sports Science of the University of Münster (ID 2020-57-MT) and pre-registered with Aspredicted.org (see https://aspredicted.org/blind.php?x=bw6cz7). This online supplement includes: a codebook describing all instructions and items, raw data (anonymised) and analysis script (Note: The raw data contains only the information of persons who were included in the analysis and have agreed to it. Some demographic information was deleted to ensure anonymity.)
Keywords: Crisis Communication; Situational Crisis Communication Model; COVID-19; Behavioral guidelines; Trust